CONCEPT OF DEPRECIATION ACCOUNTING HELD BY THE UNITED STATES SUPREME COURT. - Flewellen, W. C. (The Accounting Review, 1960)
Abstract Accountants have an obligation to explore all possibilities for the most useful methods of accounting for depreciation. Accounting literature has been filled with treatises on the pros and cons of depreciation based on historical cost as opposed to depreciation adjusted by one of the many methods recommended. The present position of the U.S. Supreme Court on depreciation accounting and the historical development of its thinking provide needed background for much of the discussion that is being conducted on the important depreciation question. The Supreme Court has accepted original cost to the owner as an appropriate basis for the determination of income and for the calculation of depreciation charges. In accepting this generalization, however, diversity of opinions in dividend cases must be kept in mind. One must also recognize that the Court will not disturb the findings of the various Commissions. The Commissions are at present firmly committed to a cost basis but should they change, it appears not unlikely that the courts will approve other bases so long as they do not appear to be confiscatory.